A One-Step Immunostaining Method to Visualize Rodent Muscle Fiber Type within a Single Specimen. - Shoko Sawano; Yusuke Komiya; Riho Ichitsubo; Yasuyuki Ohkawa; Mako Nakamura; Ryuichi Tatsumi; Yoshihide Ikeuchi; Wataru Mizunoya (PLoS ONE, 2016)
In this study, we present a quadruple immunostaining method for rapid muscle fiber typing of mice and rats using antibodies specific to the adult myosin heavy chain (MyHC) isoforms MyHC1, 2A, 2X, and 2B, which are common marker proteins of distinct muscle fiber types. We developed rat monoclonal antibodies specific to each MyHC isoform and conjugated these four antibodies to fluorophores with distinct excitation and emission wavelengths. By mixing the four types of conjugated antibodies, MyHC1, 2A, 2X, and 2B could be distinguished within a single specimen allowing for facile delineation of skeletal muscle fiber types. Furthermore, we could observe hybrid fibers expressing MyHC2X and MyHC2B together in single longitudinal muscle sections from mice and rats, that was not attained in previous techniques. This staining method is expected to be applied to study muscle fiber type transition in response to environmental factors, and to ultimately develop techniques to regulate animal muscle fiber types.